Newly Diagnosed SLE With APLS and Right Atrial Thrombus - Ilya Ivyanskiy MD; Shady Abdelbaki MD; Muhammad Mohsin Qayyom MD; Robin Horn MD; Nicole Davey-Ranasinghe MD (SAGE Publishing, 2023)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder manifesting in myriad of forms and could affect almost any body system or organ. Antiphospholipid syndrome (APLS) is a relatively common scenario in SLE. Both arterial and venous thrombosis is a hallmark feature of APLS. Among others, intracardiac thrombus is a rare and potentially life-threatening presentation. It could occur in any heart chamber whereas the right atrium is the least common location. The treatment is based on anticoagulation preferably with warfarin along with treatment of SLE. We describe a young patient with newly diagnosed SLE with APLS complicated by right atrial thrombus formation. We are, therefore, adding to the scant literature on right atrial thrombi in SLE and increasing awareness of readers of this serious and potentially deadly condition if left unrecognized.